The Rising of the Gauchesca Literature in Río de la Plata: Social Change and Cultural Negotiations (1770-1820) - Peire, Jaime Antonio (2018)
The increasing importance of the Atlantic made Buenos Aires became more relevant as port of that space that was changing of meaning during the XVII and XVIII centuries. That fact produced an internal migration, primarily, of mestizo, indigenous and caste population, most of which circulated in that “new” space from Rio Grande do Sul to the Rio de la Plata area. Literature reflected the emergence of these characters, later named as gaucho or gaúcho. It captured their language and life in a new literary genre : the “gauchesca”. In the form of minor lyrical compositions, sainetes  cielitos and dialogues, endured from the last third of the XVIIIth century until now, although the “gaucho” suffered great modifications in symbolic and political representations. This paper studies the beginning of this new  genre –that cannot be ignored- as the historical birth of an alternative identity circle perhaps most egalitarian. It attends to the responsiveness of the language and analyzes its believability and negotiation with the elites, since them intended to control a workforce that was essential to the estancias but also to the army.